(untitled) (Alexandria, 1994)
Book is the sequels to Clinical Preventive Services...explains how to put the recommendations of the CPS into practice... this is the new standard for outpatient medicine services
Keywords: Y học lâm sàng,Preventive health services,Clinical medicine,Các dịch vụ y tế dự phòng; Cẩm nang, sách hướng dẫn, v.v,Handbooks, manuals, etc,Handbooks, manuals, etc,Cẩm nang, sách hướng dẫn, v.v